Vicious Metaphysics? - Anke Jahn; Thor Hennelund Nielsen (Philosophy of Medicine, 2026)
Recent developments in the debate on epistemic injustice have expanded the original concept to include abstracta as epistemically unjust. Drawing on these arguments, we propose to distinguish between inherent conceptional epistemic injustice and contingent conception-mediated epistemic injustice. Applying this distinction to mind-body dualism in medicine, we argue that it falls within the latter category. Dualistic patterns can be found in organizational structures, research methodologies, and beliefs among clinicians and patients. The mutual reinforcement of these different dimensions systematically promotes epistemic injustices, especially toward patients whose ailments resist a clear categorization as either mental or somatic.